2020
DOI: 10.2147/oarrr.s269889
|View full text |Cite
|
Sign up to set email alerts
|

<p>Psychological State and Associated Factors During the 2019 Coronavirus Disease (COVID-19) Pandemic Among Filipinos with Rheumatoid Arthritis or Systemic Lupus Erythematosus</p>

Abstract: Background: Patients with systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) are perceived to be more vulnerable to worse COVID-19 infection outcome. Furthermore, severe shortage in hydroxychloroquine supply was experienced. Objective: We presented the psychological responses of Filipino SLE and RA patients to the COVID-19 pandemic and shortage of hydroxychloroquine supply. Methods: A total of 512 completed online surveys from SLE and RA patients were gathered from May 19 to 26, 2020. The online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 40 publications
3
57
0
Order By: Relevance
“… 249 In addition, in a cohort of patients with rheumatoid arthritis and SLE in the Philippines, a considerable proportion of patients were experiencing moderate to severe stress (12%), moderate to extremely severe anxiety (39%), and depression (28%). 250 …”
Section: Ancestral Background Socioeconomic Factors and Indirect Conmentioning
confidence: 99%
“… 249 In addition, in a cohort of patients with rheumatoid arthritis and SLE in the Philippines, a considerable proportion of patients were experiencing moderate to severe stress (12%), moderate to extremely severe anxiety (39%), and depression (28%). 250 …”
Section: Ancestral Background Socioeconomic Factors and Indirect Conmentioning
confidence: 99%
“…The ongoing outbreak, strict isolation measures and the suspension of attendance at schools, colleges, and universities across the country is believed to have an impact on the mental health of students. There have been reports on the psychological impact of the epidemic on the general public, patients, medical staff, children, and older adults (Chen et al, 2020 ; Golberstein et al, 2020 ; Hao et al, 2020 ; Tee, Salido, et al, 2020 ; Wang, Pan, Wan, Tan, Xu, Ho, & Ho, 2020 ; Yao et al, 2020 ). However, no evidence of in-depth research on the specific mental health challenge to university students as a result of the global health crisis has been published to date (Cao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, patients with rheumatological diseases, who are prone to psychological disorders, are likely to be easily psychologically affected by the COVID-19 outbreak. Recent studies have shown that patients with RA, Axial Spondyloarthritis, Lupus, and Behçet Disease were severely affected by the COVID-19 pandemic [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%